The Role of PPAT in the Sale and Purchase of Disputed Land Rights - Christina Winarni (Sultan Agung Notary Law Review, 2022)
The purpose of this study was to identify and analyze the role of the PPAT in the sale and purchase of disputed land rights in Klaten Regency. To find out and analyze the juridical role of the PPAT in the sale and purchase of disputed land rights in Klaten Regency. Juridical research methods. The type of research that will be used by the author is empirical juridical research. Qualitative approach and data analysis using qualitative. The results of the study show that the official authorized to make the deed is the PPAT. The Land Deed Making Officer (PPAT) is a General Official who is authorized to make authentic deeds regarding certain legal actions regarding land rights or ownership rights to Flats Units, and has the authority to make Sale and Purchase Deeds (AJB) which is proof that there has been sale and purchase of land The factors that led to the making of a land sale and purchase deed by the PPAT which then resulted in a land dispute were as follows: required sale and purchase transactions. There is a very high sense of mutual trust among fellow PPATs and between the parties and the PPAT. The time and busyness of the parties causes the PPAT to adjust to the time and busyness of the parties. The big factor is the value of the sale and purchase transactions carried out by the parties so that the PPAT is willing to follow the wishes of the parties. Relationship and friendship factors Based on the above study, it can be concluded, first, the form of responsibility of the Land Deed Official in providing legal protection to the parties is by fulfilling the rights and obligations of the seller and the buyer since the signing of the sale and purchase deed before him (PPAT), the transfer process is registered land rights, until after receiving the land title certificate according to what the buyer wants, and in the future there will be no lawsuits and demands in any form and from any party due to a change in ownership of the land rights, so the buyer feels safe in buying the land, Likewise, sellers are safe in selling their land rights.